2019
DOI: 10.1002/ppp.2027
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term role of cooling the underlying permafrost of the crushed rock structure embankment along the Qinghai–Xizang railway

Abstract: Understanding the long‐term role of cooling the underlying permafrost of the crushed rock structure embankment (CRSE) along the Qinghai–Xizang Railway (QXR) is crucial for the railway's safe operation. The thermal regime of the permafrost under the CRSE is analyzed here using monitoring data of soil temperature from 2005 to 2015. The results show that the CRSE plays an important long‐term role in cooling the underlying permafrost under the present climate change conditions; however, different types of CRSEs ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 43 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…Different types and shapes of air convection embankments (ACEs) have been used in Alaska (Thompson Drive 129 ), Canada (Alaska Highway 130 ; Puvirnituk airstrip 131 ), and China 29,132 . For QTR observations showed that embankments with crushed rock structure can adapt to a climate warming of 1.0°C 40,133 .…”
Section: Mitigation Methodsmentioning
confidence: 99%
“…Different types and shapes of air convection embankments (ACEs) have been used in Alaska (Thompson Drive 129 ), Canada (Alaska Highway 130 ; Puvirnituk airstrip 131 ), and China 29,132 . For QTR observations showed that embankments with crushed rock structure can adapt to a climate warming of 1.0°C 40,133 .…”
Section: Mitigation Methodsmentioning
confidence: 99%
“…The cooling process of the crushed-rock layer is mainly based on the convective heat exchange of air in winter and thermal insulation in summer (Zhang et al, 2006;Cheng et al, 2007;French, 2007;Ma et al, 2008;Mu et al, 2010a). However, it has also been shown that the cooling effect of the CRE is better in the cold permafrost zone and less effective in the warm permafrost region (Ma et al, 2013;Mu et al, 2018;Wu et al, 2020). Most of the permafrost zone of the QTR adopts the CRE; there are still some permafrost zones for the traditional embankment (TE).…”
Section: Introductionmentioning
confidence: 99%
“…Based on ground temperature and deformation data, the researchers analysed the thermal response of permafrost under the embankment to climate and human activity [15][16][17]. Furthermore, by comparing the thermal stability and deformation stability of different embankment forms, the cooling ability of each structure is evaluated [5,[18][19][20]. However, due to the limitations of field conditions and the lack of enough monitoring data, methods such as numerical simulations other than field monitoring have also been used to study the embankment stability in permafrost regions.…”
Section: Introductionmentioning
confidence: 99%